ANTIBIOTIC RESISTANCE AND VIRULENCE PROFILES OF AEROMONAS POPULATIONS FROM BEACH AND POST-CHLORINATED WASTEWATER COMPARED TO CLINICAL ISOLATES IN MILWAUKEE, WISCONSIN, USA - (:unkn) unknown (My University, 2024)
Aeromonas spp. are recognized as emerging human pathogens associated with gastroenteritis, wound infections, and bacteremia. Considering its ubiquitous nature in aquatic environments, many of these diseases arise from direct or indirect aquatic exposure. However, comparisons of Aeromonas populations among environmental sources compared to clinical populations are rarely reported. Therefore, our objective was to compare environmental Aeromonas populations from treated wastewater effluents and neighboring recreational beaches to clinical strains from the same geographical locations to assess the potential health risk. Environmental Aeromonas isolates were acquired from beaches and post-chlorinated wastewater (POC) using ampicillin dextrin agar with vancomycin and irgasin (ADA-VI). Antibiotic susceptibility was determined using Kirby-Baur disk diffusion with subsequent analysis of ARGs using PCR. To assess the clinical relevance of environmental isolates, we identified the species and virulence potential. Species were identified using gyrB PCR amplification and sequencing of subpopulations of clinical, POC, and beach isolates. Our findings identified clinical and POC populations as the most similar antimicrobial resistance (AMR) profiles except for nalidixic acid resistance (10.5% to 42.9% respectively), while beach isolates had the highest antibiotic susceptibility. Statistical differences among sources (P